2007
DOI: 10.1108/09513550710750011
|View full text |Cite
|
Sign up to set email alerts
|

Negative behaviours in the workplace

Abstract: Purpose-The purpose of this paper is to draw attention to the need to treat negative workplace behaviours which are not perceived as bullying as seriously as those which are. The paper also aims to examine whether or not the National Health Service (NHS) appears to experience a higher level of negative behaviour than private sector organisations and whether lower frequency behaviour has similar levels of effect as higher frequency behaviour. Design/methodology/approach-A mixed-method approach is used whereby a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…In contrast, Time 2 coworker incivility was negatively correlated with Time 2 work effort (r ϭ Ϫ.30). These outcomes replicate previous studies which found that targets of workplace incivility tend to report affective (Pearson et al, 2001) and behavioral strains (Burnes & Pope, 2007;Penney & Spector, 2005).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, Time 2 coworker incivility was negatively correlated with Time 2 work effort (r ϭ Ϫ.30). These outcomes replicate previous studies which found that targets of workplace incivility tend to report affective (Pearson et al, 2001) and behavioral strains (Burnes & Pope, 2007;Penney & Spector, 2005).…”
Section: Resultssupporting
confidence: 91%
“…For example, Burnes and Pope (2007) reported that more than one third of employees have either witnessed or experienced incivility incidents at least several times a month. Nevertheless, only a fraction of incivility targets file a formal complaint (i.e., 6%; Pearson & Porath, 2009).…”
Section: Workplace Incivilitymentioning
confidence: 97%
See 1 more Smart Citation
“…Similar findings have been reported globally in a range of public sector occupations, such as medical work (Quine, 1999;Burnes and Pope, 2007;Bentley et al, 2009), education (Fox and Stallworth, 2005;Lewis et al, 2009) and public administration (Fevre et al, 2012). Violence also features strongly in numerous studies, with health and social work and public administration faring particularly badly as a result of violent encounters with members of the public (European Foundation for the Improvement of Living and Working Conditions, 2007;Jones et al, 2011).…”
Section: Workplacesupporting
confidence: 56%
“…This issue is compounded when viewing (as we do) health-care organisations as comprising multiple cultures/cultural frames, rather than as a single culture of care. These points notwithstanding, research indicates that five aspects of culture are of particular salience to patient safety: (1) the need for a culture of compassion in care; 81 (2) the problematic intra-and interprofessional hierarchies, which privilege a perceived elite at the expense of the broader health-care team; 41,[90][91][92] (3) the culture of blame that retards the promotion of adverse incident reporting and disclosure of harm to patients; 42,[93][94][95] (4) the culture of bullying [96][97][98] that, regrettably, appears to be widespread across the NHS; [99][100][101][102][103][104] and (5) the culture of unrelenting pressure to attain government targets, which creates a range of unintended and dysfunctional consequences.…”
Section: Culture(s) Of Carementioning
confidence: 99%